A Gestão da Marca na valorização de uma empresa de artesanatos regionais - França, Evellin Lemos (Brasil, 2024)
Regional handicrafts represent the culture of a certain region, bringing to mind in every detail of its construction the techniques and traditions of the native peoples. Considering the importance of regional handicrafts, the present work consists of a case study of the Amazonian handicraft products store, Arteam. The project aims to demonstrate the importance of design in the creation of value for a company, through the development of brand identity in its conceptual and visual aspect. The project was developed using the methodology proposed by the Design Council, the Double Diamond, which is composed of the stages discover, define, develop and deliver. As a result, the translation of the essence of the brand and the creation of a new visual identity were obtained, which represents it in all its dimensions and the grouping of information in the Brandbook, evidencing the management of design as an important factor in the valorization of a brand.